Adaptive remodeling of renal Na+ and K+ transport during pregnancy. Issue 5 (September 2018) - de Souza, Aline M.A.; West, Crystal A.
Abstract : Purpose of review: Renal ion transport undergoes dramatic changes during the course of gestation. These adaptations are necessary to meet the dynamic requirements of pregnancy and support fetal development. Pregnancy is characterized by a high demand for both sodium and potassium. Recently there has been work in the field profiling the modifications of the renal tubules in pregnancy to meet these demands. The purpose of this review is to summarize these findings. Recent findings: The work to date suggests an important role for the distal nephron in both the renal sodium and potassium reabsorption during pregnancy. There is strong evidence that renal sodium reabsorption is mediated by the epithelial sodium channel (ENaC). Whereas renal potassium reabsorption is mediated by upregulation of potassium retaining transporters (HKA2) and downregulation of potassium secreting channels (ROMK, BK). Summary: Fetal growth restriction and hypertensive disorders of pregnancy including preeclampsia are marked by suboptimal maternal plasma volume expansion, which is determined by renal electrolyte handling. Therefore, understanding the physiologic demand for sodium and potassium in pregnancy and the adaptations required to support these needs is necessary for the effective treatment of diseased states of pregnancy.